Measuring and analyzing the Super-Efficiency of industrial companies: an applied study in the Iraq Stock Exchange (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to measure and analyze the superior efficiency of industrial companies,which listed in the Iraq Stock Exchange for the period (2017-2019), by using ES-DSMmodel, and Lingo 18 software, the data of (15) industrial companies were used, thisstudy depend on two approaches they are:(total of assets and total expenses), and twooutputs they are: (share price and total revenue).The study explored that there are sevencompanies that achieved 100% efficiency in 2017, five of them achieved superiorefficiency, as (IBPM) which gain first ranked, while (IICM) and (IIEW) ranked last. In2018, also seven companies achieved an efficiency rate of 100%, five of them alsoachieved superior efficiency, where (IBSD) ranked first, while (IICM) and (IIEW)ranked last, on the other hand, there were six companies that achieved an efficiency rateof 100% in 2019, four of them achieved maximum efficiency, and the first rank goes to(IBPM) company.And the last rank goes to the companies of both (IICM) and (IIEW),also, IBPM company achieved the first place during the study period, according to ESDSMtest, while IBSD ranked at second place, on the other hand, IBSD achieved thefirst place during (2017-2019), which achieved superior efficiency, while (IBPM) and(IMOS) were in the second place to become the best two companies that othercompanies can consider them as a typical companies